Die Industrie Australiens in den achtziger jahren: Entwicklung, Probleme und Fördermaßnahmen - Wadley, David; Grotz, Reinhold (ERDKUNDE, 1988)
This paper reviews Australian industrial development and policy in the changed global environment of the 1980s. Focusing first on macroeconomics, it cites Australia’s declining terms of trade and balance of payments, currency devaluation and budget deficits as a backdrop to recent performance in the secondary sector. Before 1980 manufacturing was small-scale by world standards, inward looking and heavily protected. In the present decade this produced a cessation of growth in factory numbers and a significant loss of jobs. A squeeze on profitability inhibited capital investment, which in turn depressed productivity. At the same time structural change by industry subdivision and geographical change by State and region were of some importance. Industrial policy is assessed at Federal and State levels. Federal measures, mostly macroeconomic in scope, have been dominated historically by the tariff, though recently other sectoral interventions have been undertaken. The bearing of macroeconomic monetary policy is discussed, as is the role of various micro initiatives instigated in the last four years. At the State level a rather ouverdue focusing of policy is noted, which may allow sectoral discrimination: by contrast, non-discriminative ’decentralisation’ assistance has been largely replaced by local area economic development strategies. The positive steps taken by States to facilitate investment in high technology are also favourable reported. The national industry debate is seen in terms of three publications issued in the last twelve months, one from an industry council, one reflecting trade union interests and the last from an academic economist. Export activity emerges as a possible strategy for industrial revitalisation but, as is pointed, it will pose significant problems in economic management at both the firm and national levels.